Enhanced Coplanarity and Giant Birefringence in Hydroxypyridinium Nitrate via Hydrogen Bonding between Planar Donors and Planar Acceptors - Yin, Jian‐Ping; Guo, Jingyu; Huo, Hao; Liu, Xin; Cheng, Xue‐Jie; Lin, Zheshuai; Wu, Li‐Ming; Chen, Ling (Angewandte Chemie International Edition, 2025)
Birefringent crystals, which possess optical anisotropy, are important optical components. However, designing and synthesizing birefringent crystals faces the challenge of achieving anisotropic structures, especially coplanar geometries. Herein, we achieve a significant birefringence in an ionic compound (C5H6ON)+(NO3)−, (4‐hydroxypyridinium nitrate, 4HPN) by hydrogen bonding between planar donors and planar acceptors. We demonstrate that the interactions between the planar hydrogen bond donor ((C5H6ON)+) and planar hydrogen bond acceptor ((NO3)−) ensure the coplanarity during the crystal packing, generating the desired giant optical anisotropy. On two manually cut crystal chips, we observe a Δnobv. ${Δ {n}^{obv.}}$ =0.494 ( Δnmaxcal. ${Δ {n}_{max}^{cal.}}$ =0.593), which is the largest among nitrates, or hydroxypyridinium derivatives. This Δnobv. ${Δ {n}^{obv.}}$ value already surpasses those of the benchmark crystals, e.g., YVO4 and CaCO3, commonly used in the UV to visible and near IR spectral range. 4HPN also exhibits a strong second harmonic generation response (9.55×KDP). This strategy offers a promising avenue for the design and development of birefringent crystals with potential applications in optical communication, sensing and signal processing devices. A strategy that utilizes hydrogen bonding between planar donors and planar acceptors is proposed. Guided by this stratedy, the giant birefringence achieved by ionic crystal, (C5H6ON)+(NO3)−, 4HPN, is achieved. This concept has convincingly demonstrated its applicability and relevance across a diverse array of systems, providing a guiding principle in design synthesis.